2009
DOI: 10.3899/jrheum.090101
|View full text |Cite
|
Sign up to set email alerts
|

Effective Anti-TNF-α Therapy Can Induce Rapid Resolution and Sustained Decrease of Gastroduodenal Mucosal Amyloid Deposits in Reactive Amyloidosis Associated with Rheumatoid Arthritis

Abstract: Our results indicate a striking effect of anti-TNF therapy for rapid removal and sustained disappearance of amyloid deposits in gastric mucosal tissue with amelioration of renal functions in patients with reactive amyloidosis due to RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 36 publications
2
36
0
3
Order By: Relevance
“…As described elsewhere, etanercept treatment of patients with AA amyloidosis produced a decrease in SAA, but there were no significant changes in serum creatinine or proteinuria (Perry et al, 2008). In 2009, Kuroda et al reported the effect of TNF inhibitors on 14 patients with AA amyloidosis associated with RA (Kuroda et al, 2009). For the 4 patients treated with infliximab and 10 patients with etanercept, creatinine clearance improved in 4 patients, did not change in 5 patients, and deteriorated in 3 patients.…”
Section: The Clinical Effect Of Tocilizumab and Other Biologics On Aamentioning
confidence: 84%
“…As described elsewhere, etanercept treatment of patients with AA amyloidosis produced a decrease in SAA, but there were no significant changes in serum creatinine or proteinuria (Perry et al, 2008). In 2009, Kuroda et al reported the effect of TNF inhibitors on 14 patients with AA amyloidosis associated with RA (Kuroda et al, 2009). For the 4 patients treated with infliximab and 10 patients with etanercept, creatinine clearance improved in 4 patients, did not change in 5 patients, and deteriorated in 3 patients.…”
Section: The Clinical Effect Of Tocilizumab and Other Biologics On Aamentioning
confidence: 84%
“…However, it has been recently disclosed that dynamic turnover of constituent proteins does occur in these lesions and that amyloid deposits can regress if the supply of amyloid precursor is halted by treatment (22). In patients with familial amyloid polyneuropathy and AA amyloidosis, clear regression of tissue amyloid deposition after treatment is seen in the abdominal fat pad (23) or gastroduodenal mucosa (24,25), and similar findings have been reported in AL amyloidosis patients (8,9). With regard to hepatic amyloidosis, however, regression has only been demonstrated radiographically (26,27), not histopathologically, except for one case in which histological regression was observed 5.5 years after treatment (12).…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the efficacy of anti-TNF therapy has been reported in many papers and reports given at academic society meetings. Kuroda et al (2009) and Nakamura et al (2010) reported efficacy in a large number of patients over a short time. Kuroda et al analyzed therapeutic results in 14 RA patients complicated with AA amyloidosis in whom RA treatment was effective (four were given infliximab and 10 were given etanercept; mean www.intechopen.com Optimal Treatment Strategy for Amyloid A Amyloidosis in Rheumatic Diseases -Anti-Interleukin-6 Receptor Therapy 159 observation period: 20.1 months).…”
Section: Treatment Of Aa Amyloidosis With Biologicsmentioning
confidence: 99%
“…In a 24-h proteinuria assay, three patients showed decreased proteinuria, six were unchanged, and three became worse, indicating that progression of renal disorders was prevented in about 70% of patients. In nine patients subjected to serial gastroduoedenal biopsies, the level of amyloid deposits in the tissue was reported to decrease significantly (Kuroda et al, 2009). Nakamura et al (2010) used etanercept to treat 14 Japanese patients who had the SAA1.3 allele and high susceptibility to AA amyloidosis (mean observation period: 19 months) and analyzed their renal function profiles.…”
Section: Treatment Of Aa Amyloidosis With Biologicsmentioning
confidence: 99%